2020
DOI: 10.3389/fpls.2020.00633
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric Organic Acids as Biostimulants: Monitoring Feedbacks on Soil Microorganisms and Biochemical Properties

Abstract: pH (H 2 O) 7.9 ± 0.2 CO 3 −2 (g kg −1) 204 ± 10 Fine sand (g kg −1) 139 ± 33 Coarse sand (g kg −1) 385 ± 24 Silt (g kg −1) 244 ± 17 Clay (g kg −1) 232 ± 9 Clay types Smectite 64% Kaolinite 24% Illite 12% Organic matter (g kg −1) ± 0.4 Humic acid-C (mg kg −1) 18.2 ± 2.6 Fulvic acid-C (mg kg −1) 9.6 ± 1.3 Total N (g kg −1) 0.5 ± 0.2 Olsen P (g kg −1) 8.6 ± 0.9 Fe (mg kg −1) 35.6 ± 3.8 Cu (mg kg −1) 9.5 ± 1.2 Mn (mg kg −1) 11.1 ± 2.4 Zn (mg kg −1) 8.3 ± 1.3 Cd (mg kg −1) 6.2 ± 1.5 Pb (mg kg −1) 0.39 ± 0.15 Ni (mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 90 publications
2
69
0
Order By: Relevance
“…TCP induces fungi to produce OA. The capacity to solubilize complex phosphates is mainly attributed to the synthesis of OA, which is produced through the cellulose-decomposition [ 9 , 15 ]. An earlier study stated a significant correlation between the gradual decrease in pH and the release of OA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TCP induces fungi to produce OA. The capacity to solubilize complex phosphates is mainly attributed to the synthesis of OA, which is produced through the cellulose-decomposition [ 9 , 15 ]. An earlier study stated a significant correlation between the gradual decrease in pH and the release of OA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process could be related also to the production of CA, which decreases the pH within a range that does not favor the growth of the pathogen, reducing the cytoplasmic pH and stopping metabolic activities. On the other hand, OA acts on the neutralization of the electrochemical potential and increases the permeability of the plasmic membrane, leading to the death of the pathogen [ 15 , 20 , 52 ]. In the many studies about the antimicrobial effect of CA, it was reported that CA possesses a stronger inhibitory impact compared to lactic and acetic acids [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mondala et al (2017) reported that 2:1 and 1:1 (molar ratios) oxalate-citrate mixtures were able to release up to 61% of total bound P from sediments. LMWOAs are used by rhizosphere microorganisms as sources of carbon and energy, and citric acid favored the proliferation of the Clostridiaceae, Micrococcaceae, and Pseudomonadaceae families (Macias-Benitez et al 2020). In addition, the enhanced release of P from various P-bearing minerals and rocks due to enhanced soil LMWOAs produced by various soil microorganisms, such as Penicillium spp., Talaromyces spp., Aspergillus niger, etc.…”
Section: Other Macro-and Micronutrient Release With the Lmwoas And Their Role In The P Releasementioning
confidence: 99%
“…One of the ways out of this problem is to use the potential of the soil microflora itself, as well as artificial introduction of effective organic and biological agents -biostimulants, feeding and stimulating the development of the rhizosphere and catalyzing enzymatic activity, and, accordingly, plant growth. It is also important that biological products have waterproof adhesive properties due to its specific composition, and the mechanism of artificial structure formation is realized [9,10]. The use of biostimulants based on humic acids has proven itself to increase the productivity of crops, its resistance to adverse weather conditions and increased doses of pesticides.…”
Section: Introductionmentioning
confidence: 99%